Digital literacy to improve pedagogical and professional competence of early childhood teacher - Nurul Khotimah; Muhammad Reza (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
Abstrak: Pada era transisi revolusi industri 4.0 menjadi 5,0, guru memerlukan kemampuan literasi komputer dengan kemampuan untuk mencari dan mengelola data secara digital serta mengoperasikan komputer. Para guru kemudian mengikuti Pendidikan Profesi Guru (PPG) dalam jabatan yang difasilitasi aplikasi google suite untuk guru yang profesional pada era revolusi industri 5.0. Penelitian ini bertujuan untuk mengimplementasikan kemampuan digital pada guru Pendidikan Anak Usia Dini (PAUD) dalam pembelajaran PPG PAUD dan meningkatkan kemampuan pedagogi guru PAUD. Metode yang digunakan adalah mixed method dengan pengumpulan data melalui google form, hasil wawancara, studi literatur, dan relevansi data melalui penelitian yang relevan. Hasil menunjukkan kenaikan yang signifikan pada kemampuan profesional guru PPG dalam jabatan tahap 1. Guru mendapatkan pendalaman materi pedagogi dan profesional, pengembangan perangkat pembelajaran, review perangkat pembelajaran, dan tes komprehensif. Abstract: In the transition era of the industrial revolution 4.0 to 5.0, teachers need computer literacy skills with the ability to search and manage data digitally and operate computers. On these grounds, numerous teachers take part in the teacher professional development program for in-service teachers (PPG dalam Jabatan) facilitated by the Google Suite application for professional teachers in the 5.0 industrial revolution era. This study aims to implement digital skills for early childhood education (PAUD) teachers in PPG and improve the pedagogical abilities of PAUD teachers. The method used is a mixed methods with data collection using Google Forms, interviews, literature studies, and data relevance through relevant research. The results show a significant increase in the professional ability of teachers who join stage 1 of the program. Teachers deepen the pedagogical and professional materials, development of educational materials, examination of learning material, and comprehensive tests.